Interior Design of Gubeng Train Station in Surabaya With Colonial Style Future Station Concept - Alifia Hidayati Amrina; Ambar Mulyono (Pendhapa, 2022)
Interior Design of Gubeng Train Station in Surabaya with a Concept Future Station and Colonial-Style aims to design a train station that can keep up with future Indonesian railways and maintain the identity of the Gubeng station itself, this is because the train station has an essential role in all activities of railway which is one of the main transportation options in Indonesia and one of the Heritage buildings of a city. The development of rail transportation also has an impact on the activity needs of Train Station users, which are still not fulfilled by Train Stations in Indonesia, especially in user orientation and sustainable design. This is a reason for the inconvenience and can impact on the decrease in rail transport users.The design made is expected to cover all the activities of station users and still maintain the identity of the building as a visitor attraction. Supporting all activities for station users can be achieved by paying attention to 3 important things, is accessibility, mobility, and sustainability, which are the main concepts in this design, apart from the functional factors, this building will be designed in a colonial style as the identity of the previous Gubeng Station which is also a Heritage building in Surabaya.